Implementation of Internship Practices and Student Literacy Regarding ShariaBanking on Work Readiness in Sharia Bank - Ferri Alfadri (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2023)
This study aims to determine how much influence work practices and student literacy have on understanding Islamic banking on work readiness in Islamic banks after graduating from college. This type of research is field research with a quantitative approach. The sample used in this study was 74 respondents using statistics, namely SPSS Version 23. Based on the results of the partial test in this study, there is an influence of apprenticeship practices on work readiness in Islamic banks. But the literacy variable has no effect on work readiness. then this will become input and evaluation material to further improve the quality of the faculty whether it is in accordance with the vision and mission of the university